2014
DOI: 10.1155/2014/349249
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram and Alzheimer’s Disease: Clinical and Research Approaches

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder that is characterized by cognitive deficits, problems in activities of daily living, and behavioral disturbances. Electroencephalogram (EEG) has been demonstrated as a reliable tool in dementia research and diagnosis. The application of EEG in AD has a wide range of interest. EEG contributes to the differential diagnosis and the prognosis of the disease progression. Additionally such recordings can add important information related to the drug effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 93 publications
(113 reference statements)
1
50
0
1
Order By: Relevance
“…Consequently, EEG markers may be more sensitive than structural MRI markers (which measures volume of neurons) at early stages in the disease process (Babiloni et al, 2016). Abnormal EEG patterns in dementia are well-documented (Tsolaki, Kazis, Kompatsiaris, Kosmidou, & Tsolaki, 2014). Typically, people with AD exhibit an increase in slow wave activity; that is, greater activity in lower frequency bands such as delta (1-4 Hz) and theta (4-8 Hz) and reduced activity in higher frequency bands such as alpha (8-13 Hz) and beta (13-30 Hz) (Musaeus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, EEG markers may be more sensitive than structural MRI markers (which measures volume of neurons) at early stages in the disease process (Babiloni et al, 2016). Abnormal EEG patterns in dementia are well-documented (Tsolaki, Kazis, Kompatsiaris, Kosmidou, & Tsolaki, 2014). Typically, people with AD exhibit an increase in slow wave activity; that is, greater activity in lower frequency bands such as delta (1-4 Hz) and theta (4-8 Hz) and reduced activity in higher frequency bands such as alpha (8-13 Hz) and beta (13-30 Hz) (Musaeus et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…EEG recordings can be led while a patient is inside the MR scanner. EEG and fMRI are utilized together, for occurrence, to restrict where in the cerebrum a seizure begins and where it spreads from that point [25,26] …”
Section: Electro Encephalon Graphmentioning
confidence: 99%
“…This is the reason why some clinicians recommend that all AD patients be studied at least once by EEG as well as by MRI. 27 There is a big correlation of EEG findings with other reliable biomarkers such as sMRI, even in MCI patients. Moretti et al 28 in their recent study showed that MCI subjects with higher a3/a2 ratios when compared with subjects with lower and middle a3/a2 ratios showed minor atrophy in the ventral stream of the basal ganglia (head of the caudate nuclei and accumbens nuclei bilaterally) and of the pulvinar nuclei in the thalamus.…”
Section: Electroencephalogrammentioning
confidence: 99%